Genetic analysis of a bronze age individual from Ulug-depe (Turkmenistan) - Guarino-Vignon, Perle; Marchi, Nina; Chimènes, Amélie; Monnereau, Aurore; Kroll, Sonja; Mashkour, Marjan; Lhuillier, Johanna; Bendezu-Sarmiento, Julio; Heyer, Evelyne; Bon, Céline (Frontiers in Genetics, 2022)
The Oxus Civilisation (or Bactrio-Margian Archaeological Complex, BMAC) was the main archaeological culture of the Bronze Age in southern Central Asia. Paleogenetic analyses were previously conducted mainly on samples from the eastern part of BMAC. The population associated with BMAC descends from local Chalcolithic populations, with some outliers of steppe or South-Asian descent. Here, we present new genome-wide data for one individual from Ulug-depe (Turkmenistan), one of the main BMAC sites, located at the southwestern edge of the BMAC. We demonstrate that this individual genetically belongs to the BMAC cluster. Using this genome, we confirm that modern Indo-Iranian–speaking populations from Central Asia derive their ancestry from BMAC populations, with additional gene flow from the western and the Altai steppes in higher proportions among the Tajiks than the Yagnobi ethnic group.